2014
DOI: 10.1200/jco.2014.32.26_suppl.93
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence patterns among T1-2N0 triple-negative breast cancer patients following mastectomy.

Abstract: Gastric cancer (GC) is the fourth most common type of cancer, accounting for an estimated one million new cases annually worldwide. Locally advanced GC often recurs, even following curative surgical resection. Therefore, there is a need for an effective adjuvant chemotherapy regimen. The aim of this trial was to investigate the maximum tolerated dose (MTD) of S-1 when administered in combination with oxaliplatin in postoperative GC patients. Oxaliplatin was administered at a fixed dose of 130 mg/m on day 1. S-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Our data showed that the SOX regimen with 130 mg/m 2 oxaliplatin was a promising regimen as the first-line chemotherapy in patients with advanced GC [ 12 ]. As adjuvant chemotherapy for postoperative GC, when combined with 130 mg/m 2 oxaliplatin every 3 weeks, 70 mg/m 2 /day S-1 for 2 weeks was the optimal dose in our phase I study [ 13 , 14 ]. We conducted this phase II study to further evaluate the tolerability and safety of SOX as adjuvant therapy after curative resection in Chinese patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that the SOX regimen with 130 mg/m 2 oxaliplatin was a promising regimen as the first-line chemotherapy in patients with advanced GC [ 12 ]. As adjuvant chemotherapy for postoperative GC, when combined with 130 mg/m 2 oxaliplatin every 3 weeks, 70 mg/m 2 /day S-1 for 2 weeks was the optimal dose in our phase I study [ 13 , 14 ]. We conducted this phase II study to further evaluate the tolerability and safety of SOX as adjuvant therapy after curative resection in Chinese patients with GC.…”
Section: Introductionmentioning
confidence: 99%
“…Of these 22 detected variants, variants in CYP2A6*7 , *10 , and *11 did not exhibit association with severe toxicity. This did not agree with the decreased enzyme activity of these variants ( http://www.cypalleles.ki.se/cyp2a6.htm ), which might be due to interactions among different variations [27] and regimen heterogeneity [28] .…”
Section: Discussionmentioning
confidence: 81%
“…All patients were treated with the same SOX regimen. Administrations of S-1 and oxaliplatin were given in our previous studies [28] , [29] , [30] . All the patients experienced prophylactic anti-emetic medications.…”
Section: Methodsmentioning
confidence: 99%
“…[ 13 ] S-1 monotherapy might be insufficient in some groups of patients (especially in the stage IIIB highly advanced group), therefore, Phase II trials have validated the feasibility of S-1 combined respectively with cisplatin, docetaxel, and oxaliplatin in the adjuvant setting showing increased effectiveness and acceptable toxicities. [ 63 64 65 ] These studies indicate that adjuvant therapy with S-1 plus cisplatin or plus docetaxel may provide a survival benefit to patients with stage III gastric cancer[ 66 67 ] [ Table 3 ]. In particular, S-1 plus docetaxel is a promising option for patients curatively operated in stage IIIB.…”
Section: S-1 In Gastric Cancermentioning
confidence: 99%